Corporate Profitability as a Driver of Sustainability: Insights from Emerging Market - Mohamad Nur Utomo; Nursia Nursia; Kaujan Kaujan; Ferica Christinawati Putri; Nunung Nurhasanah (International Journal of Business, Management and Economics, 2026)
This study analyses the relationship between corporate financial characteristics, geopolitical risk, organizational complexity, and corporate sustainability. Specifically, this study examines the effect of leverage and sales growth on profitability, the effect of profitability on sustainability, the moderating role of geopolitical risk, and the mediating role of organizational complexity. The study uses a quantitative approach with secondary data and is analysed using partial least squares-based structural equation modelling (PLS-SEM). Model evaluation is conducted through goodness-of-fit testing, collinearity, and structural path significance. The results show that leverage has a positive and significant effect on profitability, while sales growth has no significant effect. Profitability has a positive effect on sustainability, but this effect weakens significantly in conditions of high geopolitical risk. Organizational complexity has a positive effect on sustainability, but does not mediate the relationship between profitability and sustainability because profitability does not have a positive effect on organizational complexity. These findings confirm that the relationship between financial performance and sustainability is contextual and influenced by external factors. This study contributes by integrating geopolitical risk and organizational complexity in explaining the dynamics of the relationship between financial performance and corporate sustainability.